Phase transition line of solid molecular nitrogen into CG-polymeric phase - Yakub, L.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The coexistence line of two high-pressure phases of solid nitrogen: molecular and polymeric cubic gauche (CG) has been predicted using two separate equations of state. Phase transition parameters: latent heat, volume and entropy jumps were calculated. At low temperature the predicted volume jump ΔV(P) is in agreement with recent experimental data; at elevated temperatures P(T)-curve tends to the vicinity of the pressure maximum on the melting line.